Elementary Science Literacy: Implementing and Enhancing Student Skills and Outcomes - Hamidulloh Ibda; Munawaroh Munawaroh; Andrian Gandi Wijanarko (Indonesian Journal of Education and Social Studies, 2023)
The purpose of this study is to describe the implementation of science literacy through the one student one video program and the impact of science literacy learning on students' science literacy skill and science learning outcome. The research subjects were fifth grade students of Madrasah Ibtidaiyah Muhammadiyah Purwodadi, Tembarak, Temanggung, Central Java. This research is action research with data collection of observation, interview, documentation, and test question. Data analysis technique is descriptive quantitative. The result showed an increase in students' science literacy skill and science learning outcome. Sawa Sado Program notably enhanced students' science literacy skills. Group 1 achieved a maximum improvement of 100% across all measured aspects, followed by Group 2 and 3, which also displayed substantial advancements. However, Group 4 showed greater variability in results, with varying improvements across different aspects. The Sawa Sado Program has generally succeeded in boosting students' science literacy skills. Nonetheless, the varied outcomes among the groups suggest different extents and patterns of improvement. This indicates the program's effectiveness but also underscores the need for a deeper understanding of the differing outcomes.